THE EFFECT OF THE QUALITY MANAGEMENT SYSTEM ISO 9001:2008 AND THE CONTRIBUTION OF THE INTERNAL AUDIT UPON THE ORGANIZATIONAL PERFORMANCE AT LP3I (The Educational Education and Indonesia Professional Development) - Kamilah Sa’diah; Istianingsih Istianingsih (STIE Binaniaga, 2017)
This research aims to determine the effect of the quality management system ISO 9001:2008 and the contribution of the internal audit upon the organizational performance. The quality management system ISO 9001:2008 has been focusing to 8 (eight) dimensions, namely customer focus, leadership, involvement of people, process approach, management system, factual approach to decision-making, mutual beneficial supplier relationship and continuous improvement. The population of this research was LP3I employees who have received the training on ISO 9001: 2008. The sampling technique used total sampling method, where the number of samples is equal to the population. Methods of data analysis using Structural Equation Modelling (SEM), with validity and reliability testing, goodness-of fit tests and hypothesis testing. The results of this research has indicated that the quality management system ISO 9001: 2008 and the contribution of the internal audit have a significant effect on the organizational performance through the operational performance. However, the contribution of the internal audit has no effect on business performance.Keywords: Quality Management System ISO 9001:2008, Structural Equation Modelling, The Contribution of the Internal Audit.